2021
DOI: 10.1029/2020jd034106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Using Carbonyl Sulfide to Track the Urban Biosphere Signal

Abstract: Transport model adequately simulates OCS mixing ratios during marine influence in a coastal city. Modeling of OCS needs to improve characterization of transport and BL variability. The urban biosphere signal is an important contributor to simulated CO2 mole fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…A commonly used value is ∼1.6, although distribution of LRU values has been observed (Whelan et al., 2018 ). The Simple Biosphere Model (SiB3: Baker et al., 2003 ; Baker et al., 2008 ; Parazoo et al., 2020 ) calculates OCS uptake based on leaf physiology and soil properties (Berry et al., 2013 ), and has been evaluated against a variety of observational data (Commane et al., 2015 ; Glatthor et al., 2015 ; Hilton et al., 2017 ; Hu et al., 2021 ; Kooijmans et al., 2021 ; Kuai et al., 2015 ; Villalba et al., 2021 ; Wang et al., 2016 ). Similarly to LRU but on an ecosystem scale, we derived linear regression models for each biome from SIB3 GPP and SIB3 to calculate OCS plant uptake flux.…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used value is ∼1.6, although distribution of LRU values has been observed (Whelan et al., 2018 ). The Simple Biosphere Model (SiB3: Baker et al., 2003 ; Baker et al., 2008 ; Parazoo et al., 2020 ) calculates OCS uptake based on leaf physiology and soil properties (Berry et al., 2013 ), and has been evaluated against a variety of observational data (Commane et al., 2015 ; Glatthor et al., 2015 ; Hilton et al., 2017 ; Hu et al., 2021 ; Kooijmans et al., 2021 ; Kuai et al., 2015 ; Villalba et al., 2021 ; Wang et al., 2016 ). Similarly to LRU but on an ecosystem scale, we derived linear regression models for each biome from SIB3 GPP and SIB3 to calculate OCS plant uptake flux.…”
Section: Introductionmentioning
confidence: 99%
“…Mallik et al (2016) reported the first records of annual OCS mixing ratios over an Indian city, which were substantially higher than tropospheric values, and those values changed seasonally with an observed 86% drop in OCS in November when air masses changed from oceanic to continental. Villalba et al (2021) also observed changes in OCS related to air masses coming from marine and continental sources. This work highlighted the difficulty of characterizing the biosphere signal when the input masses are continental due to the heterogeneity, they present in OCS content compared to stable marine conditions.…”
Section: Introductionmentioning
confidence: 76%
“…Villalba et al. (2021) also observed changes in OCS related to air masses coming from marine and continental sources. This work highlighted the difficulty of characterizing the biosphere signal when the input masses are continental due to the heterogeneity, they present in OCS content compared to stable marine conditions.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations